The environmental crisis and African women's displacements in War Girls by Tochi Onyebuchi - Ostalska, Katarzyna (Tydskrif vir letterkunde, 2025)
The environmental crisis and African women's displacements in War Girls by Tochi Onyebuchi In the following article, I explore several types of dislocations (environmental, war, patriarchal, to name but a few) in Tochi Onyebuchi's novel War Girls (2019), analysed from the methodological perspective of Africanfuturism. The aim of the article is to show how the second wave of African future-oriented literature (diasporic in this case) looks back to the past (the Nigerian Civil War) in order to seek solutions for the ongoing current problems, such as the devastation of the natural environment, climate change, the participation of underage soldiers in military conflicts, and new forms of capitalism and neolonialisation. The novel is read via historical, sociological, and frequently anthropological sources to demonstrate how the speculative discourse can be firmly grounded in the scientific context. Additionally, I propose a feminist and utopian reading of War Girls. The text is divided into parts where key elements of Africanfuturism--such as digitalisation, nanotechnologies, Information Technology, African cosmologies, and oral tradition--are discussed in detail and are shown as existing at the same time, entangled with the past and future simultaneously, within human and more-than-human worlds. Keywords: Africanfuturism, War Girls, the environmental crisis, new technologies, posthumanism.